Characterization of Trichoderma sp. local isolate and antagonism assay against pathogen Helminthosporium sp. - PARLUHUTAN SIAHAAN; AGUSTINA MONALISA TANGAPO; STELLA DEIBY UMBOH (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Siahaan P, Tangpao AM, Umboh SD. 2024. Characterization of Trichoderma sp. local isolate and antagonism assay against pathogen Helminthosporium sp. Biodiversitas 25: 3380-3389. Trichoderma, as a biological agent, plays an important role in controlling pathogens that cause plant diseases, so it needs to be utilized properly, especially for local isolates. This research aimed to analyze the morphological, molecular and secondary metabolic characteristics of local isolates of Trichoderma fungus and test their antagonism against the pathogenic fungus Helminthosporium sp. The results showed that Tomohon local isolate of Trichoderma was identified as T. asperellum. The results of GC-MS analysis show that T. asperellum produces secondary metabolites in the form of volatile compounds from the group of volatile aldehydes, esters and ketones, as well as four fatty acid compounds, namely n-hexadecanoic acid, hexadecanoic acid, methyl ester, octadecadienoic acid, methyl ester, 9,12-octadecadienoic acid (Z,Z), play an important role in the antagonistic ability of Trichoderma. T. asperellum was able to inhibit Helminthosporium sp. by 70% on the seventh day of observation, and had antagonistic mechanisms, namely antibiosis and competition. Based on these results, local isolates of T. asperellum have great potential for use as biological control agents.